Language attitudes of Limon creole speakers - Spence Sharpe, Marva (Revista de Filología y Lingüística de la Universidad de Costa Rica, 2015)
Este estudio es un análisis de las actitudes de los hablantes del Criollo Inglés de Limón con respecto a su lengua materna. Una actitud negativa hacia esta lengua es una de las causas fundamentales de la asimilación lingüística que ocurre hoy. The following study is an analysis of Limon Creole speakers' attitudes toward their mother tongue. A non-positive attitude toward Limon Creole is one of the underlying causes for the linguistic assimilation taking place today.